Public Vices, Private Virtues? Assessing the Effects of Marketization in Higher Education - Teixeira, Pedro N.; Dill, David D.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Recent years have seen the strengthening of a discourse that emphasises the virtues of markets, competition and private initiative, vis-à-vis the vices of public intervention in higher education. This volume presents a timely reflection about the effects this increasing marketization has been producing in many higher education systems worldwide. The various chapters of this volume analyse the impact of markets at the system level, with significant attention being devoted to the changes in modes of regulation, the strengthening of aspects such as privatization and inter-institutional competition in higher education systems, and the closer interaction between higher education and its economic environment. Several of the contributors devote attention as well to the implications of market forces for institutional change, notably regarding issues such as mission, organizational structure and governance and the way marketization is affecting the internal distribution of power and the definition of priorities. Finally, the volume includes several chapters focusing on the different markets of higher education, such as the academic labour market, undergraduate and postgraduate education, and research markets. Altogether these chapters provide important insights concerning the many national and institutional contexts in which the marketization of higher education has been taking place around the world.
Keywords: Education; Education, Higher; Education; Higher Education